SEARCH HOME
 Math Central Quandaries & Queries
 Question from Kasani, a parent: evaluate the expression: -2^-1[-14 - 4(-6)] - (7 - 3)

Kasani,

I want to try a similar problem

-3-2[28 - 4(-2)] + (-7 + 5)

Some people remember the order of operations by the acronym BEDMAS.

You first need to evaluate whatever is inside the brackets or parentheses. Inside the last set of parentheses is -7 + 5 which is -2 and inside the brackets [...] is a set of parentheses (...) so I need to start with -4(-2) which is 8. Thus my first step is

-3-2[28 - 4(-2)] + (-7 + 5)
=-3-2[28 + 8] + (-2)

There is nothing more to do inside the parentheses at the end but inside the brackets is 28 + 8 which is 36 so I continue

-3-2[28 - 4(-2)] + (-7 + 5)
= -3-2[28 + 8] + (-2)
= -3-2[36] + (-2)

Now I have completed all I can do inside the brackets and parentheses so the next step is any exponents. I see 3-2 which is 1/32 = 1/9 so the next step gives me

-3-2[28 - 4(-2)] + (-7 + 5)
= -3-2[28 + 8] + (-2)
= -3-2[36] + (-2)
= -1/9 [36] + (-2)

Next is a multiplication, one-ninth times 36 which is 4 so

-3-2[28 - 4(-2)] + (-7 + 5)
= -3-2[28 + 8] + (-2)
= -3-2[36] + (-2)
= -1/9 [36] + (-2)
= - 4 + (-2)

Finally -4 plus -2 is -6 so

-3-2[28 - 4(-2)] + (-7 + 5)
= -3-2[28 + 8] + (-2)
= -3-2[36] + (-2)
= -1/9 [36] + (-2)
= - 4 + (-2)
= -6